Character Education and The Crisis of National Role Models - Sidik, Purnama; Nurihsan, Juntika; Suresman, Edy (Jurnal Pendidikan Karakter, 2024)
Character education is an essential element in building a dignified and cultured nation. Amidst the crisis of role models encompassing the nation, the implementation of character education becomes increasingly urgent. This research investigates the implementation of character education and its relation to the crisis of role models in Indonesia. The research method used is qualitative with a literature study approach. Data is collected from various sources, such as scientific journals and related resources. This study aims to analyze the factors causing the crisis of role models, identify effective strategies for implementing character education, and formulate comprehensive solutions to address the crisis of role models in our nation, including: forming a national character role model movement, strengthening the role of families in character formation, enhancing the role of schools, and strengthening the role of society especially in not becoming permissive and being concerned with character education when students are not at home and not in school